Study on Headache in ENT Practice (Bangladesh Journal of Otorhinolaryngology, 2020)
Headache is perhaps one of the commonest symptoms in all level of medical practice. Though most of the time it is very benevolent in nature. Yet, it may be the presenting symptom of a serious or/and life threatening disorder like meningitis, subarachnoid haemorrhage, stroke or brain tumor. It is this dual significance the one benign, the other potentially malignant that keeps the physician on the alert. This is a random prospective study of 120 cases of headache truly reflecting the sufferings of the victims of headache approaching the ENT specialists for the purpose to determine the exact cause of headache and get a satisfactory treatment.Bangladesh J Otorhinolaryngol; April 2017; 23(1): 19-26